Neferine alleviates chronic stress-induced depression by regulating monoamine neurotransmitter secretion and gut microbiota structure - Dong, Zaiquan; Xie, Qinglian; Xu, Feiyu; Shen, Xiaoling; Hao, Yanni; Li, Jin; Xu, Haizhen; Peng, Qiang; Kuang, Weihong (Frontiers in Pharmacology, 2022)
Neferine (Nef) might possess anti-depressive properties, but its therapeutic effects are yet to be elucidated. In this study, we aimed to explore the anti-depressant property of Nef using a chronic stress-induced depressed mice model. 15 depression-prone mice were randomly selected and divided into 3 groups, namely the model, Nef, and fluoxetine (Flu) groups. We observed that both Nef and Flu treatments significantly decreased the immobility time of depressed mice in the tail suspension and forced swimming tests, while their sucrose preference indices increased. Moreover, both Nef and Flu treatments led to a significant increase in the levels of anti-depressant neurotransmitters, like dopamine (DA), serotonin (5-HT), and norepinephrine (NE), and reduced the pathological damage to the hippocampus. Incidentally, Illumina MiSeq sequencing analysis demonstrated that the relative abundance of Lactobacillus among the intestinal microbiota of depressed mice was restored after Nef or Flu treatment. Moreover, the colonic Lactobacillus abundance was positively correlated with the levels of DA, 5-HT, and NE in the hippocampus of the mice. In conclusion, Nef improves monoamine neurotransmitter secretion and modulates the intestinal flora structure, particularly the abundance of Lactobacillus. Hence, it has a substantial anti-depressant potential, and it might act as a prospective anti-depressant therapeutic agent.